Evaluation of seed source variation in Strychnos nux-vomica L. (Kanjiram) from different forest types of Kerala - Shine G (Department of Silviculture and Agroforesty, College of Forestry, 2012)
A detailed investigation was conducted to evaluate the seed source variation in Strychnos nux-vomica L. (Kanjiram) from different forest types of Kerala through the estimation of variation in fruit traits, seed traits, germination attributes, seedling attributes, biomass estimation, alkaloid content and isozyme analysis. Identification of seed source variation of the species will be a valuable tool for its use in tree improvement programmes and by the cultivation of the tree on a commercial scale, pressure on natural stands can be reduced. The seed sources selected for the study were the dry deciduous forests of Chinnar Wildlife Sanctuary, moist deciduous forests of Pattikkad Forest Range and the riparian forests of Peechi Dam Site. The fruit parameters were tested with completely randomized design with unequal replications. The fruit traits viz. weight, volume and number of seeds per fruit, varied significantly (p<0.05) among the three seed sources and the highest values for these parameters were observed for the moist deciduous source and lowest were observed for the fruits of dry deciduous forests. The fruit weight and fruit volume were significantly correlated (p<0.01) to the number seeds per fruit. After the extraction, the seeds were categorized into four grades based on the seed size (average of the longest and its orthogonal diameter for each seed) viz., 27-30 mm, 24-27 mm, 21-24 mm and 18-21 mm. The subsequent tests on seed traits, germination attributes, seedling biomass and vigour index were done in factorial CRD and the seedling growth characteristics were tested in factorial RBD. The seeds from the dry deciduous source possessed the lowest length, width, size and weight. Seed thickness (5.3 mm) and seed density (0.53) were highest for the dry deciduous source and riparian source respectively. The regression equations were fitted for the density and weight by taking the seed size as the independent variable and were significant (p<0.05). The large sized seeds were significantly superior to the smaller ones with respect to the seed traits. The germination percentage and germination energy were similar for the dry deciduous (39%; 49%) and the riparian (38%; 44%) seed sources and were the lowest for the moist deciduous seed source (16%; 26%). Speed of germination (0.17), mean daily germination (0.54), peak value of germination (0.55) and germination value (0.34) for the dry deciduous source did not vary significantly (p<0.05) with that of riparian source; the moist deciduous source showed the lowest values. Germination attributes of larger seed grades were significantly superior compared to that of smaller seeds. From the final growth measurements it could be delineated that the seedling height (18.1 cm) was highest for the moist deciduous source and seedling collar diameter (3.6 mm) was highest for the dry deciduous source; but the riparian source produced the highest number of leaves per seedling. The seedlings from the larger seeds showed the greater growth. Seedling biomass production did not vary significantly among the seed sources and grades. Seedling vigour indices for the dry deciduous and riparian sources were significantly (p<0.05) higher to that of moist deciduous source. Highest strychnine content (3683 ppm) was obtained from the moist deciduous source and the highest brucine content (1692 ppm) was obtained from dry deciduous source. The riparian source possessed significantly (p<0.05) lowest alkaloid content. The presence of esterase was conformed in the seedling leaf extracts of all the three seed sources without any variations. Studies on different characteristics on the fruits, seeds and seedlings of Strychnos nux-vomica, revealed that the best performed seed source was the dry deciduous forest source and the poorest was the moist deciduous forest source. The results of this study will be useful in Strychnos nux-vomica for increasing the germination, seedling growth and to get higher quantities of alkaloids through breeding programmes.